2013
DOI: 10.1175/jcli-d-12-00624.1
|View full text |Cite
|
Sign up to set email alerts
|

On the Identification of the Large-Scale Properties of Tropical Convection Using Cloud Regimes

Abstract: The use of cloud regimes in identifying tropical convection and the associated large-scale atmospheric properties is investigated. The regimes are derived by applying cluster analysis to satellite retrievals of daytime-averaged frequency distributions of cloud-top pressure and optical thickness within grids of 280 km by 280 km resolution from the International Satellite Cloud Climatology Project between 1983 and 2008. An investigation of atmospheric state variables as a function of cloud regime reveals that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
73
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(80 citation statements)
references
References 47 publications
7
73
0
Order By: Relevance
“…In particular, Tan et al [] concluded that these cloud regimes are informative proxies for the various modes of convection and are empirical candidates for the building blocks of tropical convection. A further extension to these cloud regimes in Tan and Jakob [] was able to identify the major cloud regimes at a higher time resolution.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, Tan et al [] concluded that these cloud regimes are informative proxies for the various modes of convection and are empirical candidates for the building blocks of tropical convection. A further extension to these cloud regimes in Tan and Jakob [] was able to identify the major cloud regimes at a higher time resolution.…”
Section: Methodsmentioning
confidence: 99%
“…While cloud clusters are often identified by searching for large, contiguous cold cloud shields, more advanced techniques search for the combined signature of deep convection and extensive stratiform cloud and precipitation area. For example, higher stratiform rain fractions are associated with organized convection, which can be diagnosed from satellite precipitation radar data (Schumacher and Houze 2003), as are large optical thicknesses and low-cloud top pressures, which can distinguish a particular cloud regime (Tselioudis et al 2010;Tan et al 2013).…”
Section: Literature Review: Observational Studies Of Convective Organmentioning
confidence: 99%
“…Despite the fact that the occurrence of mesoscale organized convection makes up a small fraction of the total frequency of cloud/precipitation features in the tropics (\6%, Mapes and Houze 1993;Nesbitt et al 2000;Tan et al 2013), it contributes a significant proportion of total tropical cloudiness 1 and about half of total tropical precipitation.…”
Section: Literature Review: Observational Studies Of Convective Organmentioning
confidence: 99%
See 1 more Smart Citation
“…r has been chosen as a proxy for atmospheric moisture because Bretherton et al () showed an empirical exponential relationship between the variable and precipitation in the tropics. Guided by the work of Tan et al (), the modified k‐index ki=12·(Tsfc+T850)T500+12·(TDsfc+TD850)(T700TD700) is used to describe the atmospheric instability. Here T p and TDp are the air and dew point temperatures at pressure level p .…”
Section: Simulation Of Tropical Coastal Convectionmentioning
confidence: 99%